The Implementation of Fuzzy Logic Controller for Defining the Ranking Function on Malay Text Corpus - bin Rodzman, SB; Ismail, NK; Abd Rahman, N; Nor, ZM (IEEE, 2024)
Ranking is likely the most important process of an Information Retrieval (IR) system that will be used to evaluate and measure the effectiveness of an IR system. This paper aims to produce the implementation of Fuzzy Logic Controller of Mamdani-type Fuzzy Inference System for defining the ranking function by using the BM25 Model in the Malay IR System that also includes the Malay Stemmer. The result of the ranking function then will be compared to the result of Vector Space Model that is also applied in Malay IR System and be evaluated using relevant document by the Hadith expert. The results showed that FBMIR has slightly outperformed Vector Space Model on 3 Topic Set of query results such as Iman,Ilmu and Wuduk on the Precision at Rank 10 and the percentage of no relevant document in the top ten retrieved measures.